2006
DOI: 10.1107/s1744309106018136
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the synthetase domain of human CTP synthetase, a target for anticancer therapy

Abstract: PDB Reference: synthetase domain of human CTPS, 2c5m, r2c5msf.Cytidine triphosphate synthetase (CTPS) is a key enzyme in nucleic acid and phospholipid biosynthesis and its activity is increased in certain human cancers, making it a promising drug target. The crystal structure of the synthetase domain of human CTPS, which represents the first structure of a CTPS from an eukaryote, has been determined. The structure is homotetrameric and each active site is formed by three different subunits. Sulfate ions bound … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
32
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 32 publications
0
32
0
Order By: Relevance
“…At concentrations less than 0.15 mM, GTP activates Gln-dependent CTP formation by CTPS; however, at concentrations greater than 0.15 mM, Gln-dependent CTP formation is inhibited. In the absence of crystal structures of CTPS with bound GTP, it is difficult to identify potential interactions between CTPS and GTP that might contribute to this behavior (3,8,9,23). Therefore, we undertook a structure-activity study using GTP/ guanosine analogues ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…At concentrations less than 0.15 mM, GTP activates Gln-dependent CTP formation by CTPS; however, at concentrations greater than 0.15 mM, Gln-dependent CTP formation is inhibited. In the absence of crystal structures of CTPS with bound GTP, it is difficult to identify potential interactions between CTPS and GTP that might contribute to this behavior (3,8,9,23). Therefore, we undertook a structure-activity study using GTP/ guanosine analogues ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For both yeast and E. coli, CTPS exists as a dimer in the absence of ATP and UTP, but in the presence of saturating concentrations of ATP and UTP, CTPS exists as a tetramer (8,25,26). The crystal structure of the hCTPS1 synthase domain shows that it is also a dimer of dimers with a synthase domain very similar to that of E. coli (27). However, the influence of ATP and UTP on tetramerization has not been determined for either human isoform.…”
mentioning
confidence: 99%
“…Moreover, structures for the bacterial [28,29] and human [30] enzymes have been solved. The yeast CTP synthetases have high homology to bacterial and mammalian CTP synthetase enzymes [28][29][30][31][32]. All CTP synthetases identified from bacteria, parasites, yeast and mammals contain conserved CTP synthetase and glutamine amide transfer domains that are involved in catalysis (Fig.…”
Section: Ctp Synthetases Of S Cerevisiaementioning
confidence: 99%
“…All CTP synthetases identified from bacteria, parasites, yeast and mammals contain conserved CTP synthetase and glutamine amide transfer domains that are involved in catalysis (Fig. 3) [28][29][30][33][34][35][36][37][38][39]. The analysis of the Escherichia coli structure has shown that CTP synthetase has a novel product inhibition mechanism in which shared substrate and product moieties bind to a single subsite while specificity is conferred by separate sites [34].…”
Section: Ctp Synthetases Of S Cerevisiaementioning
confidence: 99%